What parents say about children's inequality of opportunities: a study in Mauritius. Issue 4 (2nd October 2017) - Morabito, C.; Carosin, E.; Vandenbroeck, M.
Abstract: Longitudinal studies showing the beneficial impact of early childhood education on later academic achievement have contributed to persuading policy-makers and academia that early childhood is the best time to address inequalities. However, the voice of parents is often absent from these debates. We investigated the perspectives of parents on children's inequalities of opportunities and on the role of education and early childhood care in equalising life chances. The study specifically explored the views of 26 parents in the sub-Saharan African country of Mauritius through focus group discussions. Findings of the study suggested that parents tend to adhere to the discourse of parental responsibility as a key factor in children's inequalities. Yet they also showed that parents have potential to criticise and deconstruct this narrative, as they experience structural circumstances, such as poverty or discrimination, shaping their life opportunities and those of their children.